2018
DOI: 10.1186/s40824-018-0129-7
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-mediated oral delivery of therapeutic DNA for type 2 diabetes mellitus

Abstract: BackgroundDiabetes mellitus (DM) is a chronic progressive metabolic disease that involves uncontrolled elevation of blood glucose levels. Among various therapeutic approaches, GLP-1 prevents type 2 diabetes mellitus (T2DM) patients from experiencing hyperglycemic episodes. However, the short half-life (< 5 min) and rapid clearance of GLP-1 often limits its therapeutic use. Here, we developed an oral GLP-1 gene delivery system to achieve an extended antidiabetic effect.MethodsHuman IgG1 (hIgG1)-Fc-Arg/pDNA comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Because of very short plasma half-life (< 5 min) and rapid metabolic clearance, the anti-diabetic effect of GLP-1 could be better utilized with oral-gene delivery methods. In this context, antibody-mediated (human IgG1 (hIgG1)-Fc-Arg/pDNA complexes were prepared as an oral-gene delivery system for the prevention of type 2 diabetes mellitus (T2DM) [218].…”
Section: Different Administration Routes Of Nanocarriersmentioning
confidence: 99%
“…Because of very short plasma half-life (< 5 min) and rapid metabolic clearance, the anti-diabetic effect of GLP-1 could be better utilized with oral-gene delivery methods. In this context, antibody-mediated (human IgG1 (hIgG1)-Fc-Arg/pDNA complexes were prepared as an oral-gene delivery system for the prevention of type 2 diabetes mellitus (T2DM) [218].…”
Section: Different Administration Routes Of Nanocarriersmentioning
confidence: 99%
“…Some previous reports also mentioned that such short treatment of GLP1 could not contribute to a significant reduction of the body weight. 2,16 However, a food uptake analysis revealed that mice treated with GLP1 started to consume less food compared to the PBS-treated mice after 1−2 doses of oral GLP1/ protamine-SMCC-Fc administration. The difference in food intake between the groups became noticeable during 32 days of study due to the effect of the delayed gastric emptying by GLP1 (Figure 5d).…”
Section: ■ Resultsmentioning
confidence: 99%
“…Diabetes mellitus is a metabolic disorder caused by the dysfunction of the pancreas, resulting in the absence or insufficient production of insulin. About 366 million people lived with diabetes in 2011, according to the World Health Organization (WHO). , There are two major types of diabetes, type 1 and type 2, in which 90% of the population is suffering from type 2 diabetes . In type 2 diabetes, the body does not use insulin properly, and the blood glucose level becomes high, which is called a hyperglycemic condition .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations